2018
DOI: 10.1002/jpln.201700350
|View full text |Cite
|
Sign up to set email alerts
|

Timely supplemental irrigation changed nitrogen use of wheat by regulating root vertical distribution

Abstract: Crop nitrogen (N) uptake depends on the root absorption area and the soil N availability which are closely related to the soil water status. With the increasing water shortages in the North China Plain, supplemental irrigation (SI) to winter wheat is a promising technique. To clarify the relationships between water and nitrogen use, four SI regimes in Tritcum aestivum L. cv. Jimai 22 were set up: no‐irrigation after emergence (T1), SI at jointing and anthesis (T2), SI at sowing, jointing and anthesis (T3), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Winter wheat seedlings are currently in the nutrient growth stage, during which the root system can compensate for reduced growth by continuously absorbing available phosphorus and alkaline nitrogen from the soil after the waterlogging stress is alleviated. Wu et al [53] concluded that soil nitrogen use efficiency was positively correlated with root length and root surface area density, similar to the results of this study. In addition, the accumulation of total nitrogen and total phosphorus in the root system of waterlogged winter wheat was 24.1% and 74.0% higher, respectively, than in the control treatment (unpublished data).…”
Section: Effects Of Waterlogging Stress On Root Morphology and Soil O...supporting
confidence: 91%
“…Winter wheat seedlings are currently in the nutrient growth stage, during which the root system can compensate for reduced growth by continuously absorbing available phosphorus and alkaline nitrogen from the soil after the waterlogging stress is alleviated. Wu et al [53] concluded that soil nitrogen use efficiency was positively correlated with root length and root surface area density, similar to the results of this study. In addition, the accumulation of total nitrogen and total phosphorus in the root system of waterlogged winter wheat was 24.1% and 74.0% higher, respectively, than in the control treatment (unpublished data).…”
Section: Effects Of Waterlogging Stress On Root Morphology and Soil O...supporting
confidence: 91%
“…In 2012–2014, the micro‐sprinkler method was adopted to irrigate the plot. The area of each plot was 4 × 23 m. The specific irrigation method and criteria for executing irrigation amounts can be found in previous studies (Wang et al, 2013; Wu et al, 2018). In 2015–2017, a basin irrigation system was implemented at the experimental site, a standard irrigation method adopted by smallholder farmers.…”
Section: Methodsmentioning
confidence: 99%
“…These suggest that tillage methods can promote root growth by improving soil structure. Previous studies usually focused on the effects of single factor (tillage or irrigation) on root growth of winter wheat 33 36 . However, there are few literatures about double factors and their interactions on root structures in different soil layers of winter wheat in lime concretion black soil.…”
Section: Discussionmentioning
confidence: 99%